Strength and Environmental Properties of Cemented Paste Backfill That Contains Sodium Silicate - Mohammad Pour, Hoda (Université d'Ottawa / University of Ottawa, 2020)
Mining is an important industry that plays a significant role in the development of human civilization and economies. However, the underground mining process produces a large volume of mine wastes (e.g., tailings) as well as creates large voids that require filling, typically with an engineering backfill material. Filling the voids with mine waste materials provides an environmental-friendly way of disposing mining waste. It is also an effective way of increasing ore recovery and improving the safety of miners. One of the best techniques of mine backfill is called cemented paste backfill (CPB), which is typically a mixture of tailings, binder and water. The most common binder used in the preparation of CPB is Portland cement (PC). PC is not only a costly binder, but its production is highly energy-intensive and also generates a large amount of CO2. The cement consumption can represent up to 75% of the cost of CPB. These above-mentioned factors have compelled mining companies to seek for cement alternatives that enhance the engineering properties of the CPB, decrease the cement content and reduce the carbon footprint of the mining industry. Sodium silicate is the most recent chemical additive that is proposed to reduce the binder content in CPB. Sodium silicate is an alkaline solution that is used to activate a pozzolanic material, such as cement, slag and Fly ash. However, the effect of sodium silicate on the strength and key environmental properties (permeability or saturated hydraulic conductivity, reactivity) of CPB is not well understood. The objective of this thesis is to investigate the possibility of using sodium silicate as an activator in cemented paste backfill and obtain an improvement in the aforementioned engineering properties of CPB. In order to determine the effect of the sodium silicate on backfill properties, some CPB testing methods were developed to fulfill the objectives of this research. Thus, the evolution of hydraulic, mechanical and microstructural properties of CPB samples containing sodium silicate (SS-CPB) have been tested or monitored at different curing ages (1, 3, 7, 28 and 90 days) and different CPB mixtures as well. The results of these studies show that activating CPB with sodium silicate develop CPB strength faster than CPB samples without sodium silicate. In addition, hydraulic conductivity and reactivity results show a positive change in samples containing sodium silicate compared to free sodium silicate CPB samples. Indeed, this activation leads to decreasing permeability and reactivity due to the formation of cement hydration products and acceleration of the binder hydration process. Moreover, binder type and content in the presence of sodium silicate as an alkali activator in the CPB play a significant role in lowering hydraulic conductivity and reactivity of CPB.
Keywords: Permeability; Cemented Paste Backfill; Sodium silicate; Reactivity; Strength; Mining